12 Challenges in shock management in the emergency department. (24th April 2019) - Graham, Colin A
Abstract : The diagnosis and emergency management of patients with shock (poor end organ perfusion with reduced tissue oxygen delivery, usually associated with systolic hypotension) is difficult even in optimum circumstances. The challenge is multiplied when patients have to be managed in overcrowded and poorly resourced emergency departments (ED). In Hong Kong, public hospital EDs manage over two million patient attendances annually, equivalent to 30% of Hong Kong's population. Around 30% of ED patients require emergency hospital admission, with the majority being more than 80 years old. Hong Kong's ageing population, with its associated comorbidities and polypharmacy, has inevitably contributed to rising numbers of critically ill ED patients in recent years. Shock is a major cause (and consequence) of critical illness in ED patients. Hypovolaemic shock is frequently secondary to gastrointestinal bleeding and trauma; septic shock is increasingly common due to better recognition in the ED and more patients with chronic immunosuppression. Cardiogenic shock is common, usually due to acute myocardial infarction. Optimum treatment for these patients is undoubtedly emergency revascularisation by primary percutaneous coronary intervention (PCI). Hong Kong currently does not have a regionalised or coordinated PCI service and this may contribute to the poor outcomes seen in elderly patients with cardiogenic shock. Increasingly, patients with acute on chronic heart failure often present with shock and require a coordinated specialist approach at the earliest opportunity to improve outcomes. Comprehensive collaboration between emergency medicine physicians, cardiologists, cardiothoracic surgeons and critical care services and shared clinical management are vital to optimise patient outcomes.